Effectiveness of invoice processing system to meet the on time payment objective of Chevron Bangladesh - Ahmed, Tanvir (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.